Hubungan Kelengkapan Fasilitas Bengkel dengan Hasil Belajar Praktik Sistem Rem Cakram Kelas XI Teknik Sepeda Motor (TSM) SMK Negeri Noemuti (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Vocational education requires a practice-based learning process supported by complete facilities so that students can master work competencies optimally. However, the condition of the Motorcycle Engineering workshop at Noemuti State Vocational High School shows that the completeness of the disc brake system practice facilities does not meet the ideal ratio standards, which affects the effectiveness of learning. This incompleteness has an impact on the low achievement of students' practical learning outcomes that have not reached the KKM. This study aims to describe the level of completeness of workshop facilities and the results of the disc brake system practice learning, and to determine whether there is a relationship between the two. The research approach uses a quantitative correlational method with a total sampling of 26 students. Data were obtained through observation, questionnaires, and documentation, then analyzed using descriptive statistics, normality tests, linearity tests, Pearson correlations, and coefficients of determination using SPSS 27. The results showed that the average completeness of workshop facilities was 42.27 and the results of practical learning were 42.81, both of which were in the good category. The Pearson correlation test produced a value of r = 0.960 with a significance of 0.000 (<0.05), indicating a very strong and significant relationship. The coefficient of determination (R² = 0.92) shows that 92% of the variation in practical learning outcomes is influenced by the completeness of workshop facilities. The more complete the workshop facilities, the higher the students' practical learning outcomes.